Analisis Proses Rekrutmen dan Seleksi terhadap Kinerja Karyawan - Samsudin, Acep; Prabowo, Budi; N, Ahmad Zaky; Sitanggang, Della Anzelia; Yulianti, Dewi Rahmania (Ikatan Da'i Indonesia, 2024)
The aim of this research is to examine the influence of the recruitment and selection process on employee performance in various company contexts. In this study, researchers collected data from several sources, including questionnaires distributed to a number of companies or institutions. Data analysis shows that the recruitment and selection process has a significant effect on employee performance. Quality employee candidates can result from an effective recruitment process, while a careful selection process can ensure that the selected candidates match the company's needs and criteria. In addition, this research also notes that recruitment methods that primarily use recommendations have weaknesses, such as late feedback after interviews. Therefore, it is recommended that companies consider recruitment methods, such as using print or electronic advertisements to publicize available positions. The results of this research have important implications for human resource management and companies in order to optimize the employee recruitment and selection process to improve a company's performance. Apart from that, this research also estimates other factors that influence employee performance, such as education, experience and motivation. Overall, this research helps companies manage their human resources in a competitive business environment more effectively.